Faktor-faktor yang Mempengaruhi Optimalisasi Penyidikan Kecelakaan Lalu Lintas: Studi Kasus pada Polrestabes Makassar - Ekapriani, Ekapriani (CV. Social Politic Genius (SIGn), 2024)
This research aims to examine the optimization of the implementation of traffic accident criminal investigations at the Makassar City Police Headquarters, as well as the factors influencing said optimization. The research methodology employed a combination of normative and empirical legal research. Data collection was conducted using three methods: questionnaires, documentation, and literature study. The research sample, determined using a purposive sampling technique, comprised 35 individuals. The obtained data were quantified using a quantitative descriptive analysis model and subsequently presented through frequency distribution tables. The research results indicate that the optimization of traffic accident criminal investigations at the Makassar City Police Headquarters is largely achieved through Alternative Dispute Resolution (ADR). Several factors influence the implementation of investigations, including the legal substance factor, legal structure factor, legal culture factor, public legal awareness factor, and the facilities and infrastructure factor. These five factors significantly affect the implementation of traffic accident criminal investigations. It is recommended that the police enhance their responsiveness in the processes of securing evidence, handling victims, and apprehending perpetrators, thereby ensuring legal certainty and justice. Furthermore, an increase in the number of Traffic Unit police personnel at the Makassar City Police Headquarters is deemed necessary, considering the high rate of accidents and the extensive geographical area of Makassar City.